Tinjauan Sistematis Jenis dan Efektivitas Media Pembelajaran dalam Meningkatkan Keterampilan Menyimak di Sekolah Dasar - Victor, Kristina Silvia (FKIP Universitas Palangka Raya, 2025)
Listening skills are an essential component of Indonesian language learning at the elementary school level, but they are often overlooked in practice. The lack of integrated information regarding the effectiveness of media used in listening instruction poses a challenge for teachers in selecting appropriate strategies. This study aims to examine the types of instructional media implemented and to analyze their effectiveness in optimizing elementary students’ listening skills. The study was conducted using the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. A total of 15 selected articles published between 2021 and 2025 were analyzed through the stages of identification, screening, eligibility assessment, and inclusion. The review identified various types of media used, including instructional videos, audiovisuals, children's storytelling recordings, cartoon puppets, pop-up book, Literacy Cloud, the Netado application, YouTube Riri, animated films, golek daun singkong folktales, language blocks, Kidoodle, Pictory AI, and Animaker. These media were proven effective in enhancing listening skills. Their effectiveness was demonstrated by an increase in average scores from 53% to 87%, mastery learning achievement, and statistically significant results (p = 0.001). These findings indicate that contextually selected media that align with students’ characteristics contribute significantly to strengthening listening skills. This study offers a scientific reference as well as practical benefits that can be utilized by teachers in selecting appropriate and adaptive media for listening instruction in elementary schools.